Association of internet addiction with adolescents’ lifestyle: A National School-based survey - Chan, Ying Ying; Awaluddin, S Maria; Lim, Kuang Kuay; Cheong, Siew Man; Baharudin, Azli; Ling, Miaw Yin; Sahril, Norhafizah; Omar, Mohd Azahadi; Ahmad, Noor Ani; Ibrahim, Normala (Multidisciplinary Digital Publishing Institute, 2021)
Internet addiction (IA) among adolescents is an issue of growing concern with adverse effects on adolescents’ health and social functioning. This study aims to determine the prevalence of IA among school-going adolescents in Malaysia and its associated factors—specifically, lifestyle factors. A nationwide cross-sectional school-based health survey was conducted in 2017 among 27,497 students from 212 randomly selected secondary schools. Information regarding sociodemography, lifestyle, and internet use was obtained using a self-administered questionnaire. IA was measured using the Malay Version of Internet Addiction Test (MVIAT). The prevalence of internet addiction was 29.0%. A multivariable logistic analysis revealed that inadequate fruit and vegetable intakes, consumed carbonated soft drinks at least once a day, consumed fast food at least three days/week, sedentary behavior, current E-cigarette users, and ever/current alcohol drinkers were lifestyle factors significantly associated with IA. Adolescents from urban schools, of higher school grade, and those whose parents are married but living apart were also found to have a greater risk for internet addiction. A positive association was found between IA with unhealthy dietary and lifestyle behaviors among adolescents. The modification of lifestyle factors needs to be considered while developing strategies and interventions for awareness-raising and prevention of IA among adolescents.